PENGEMBANGAN MODEL LATIHAN SMASH BOLAVOLI PADA KEGIATAN EKSTRAKURIKULER DI SMPN 12 MALANG - Izzul Muttaqin; M. E. Winarno; Agung Kurniawan (Fakultas Ilmu Keolahragaan UM)
ABSTRACT: The aim of this study was to develop a product that is a model exercise smash on extracurricular activities in SMPN 12 Malang. The method used in this study refers to the development model of research and development Borg and Gall. Of the ten development measures proposed by Borg and Gall, researchers used seven steps. The results of the analysis stated 79.16% volleyball game expert, expert coaching volleyball 83.33%, 80.35% and media expert, said good. Product development is feasible to use in extracurricular SMPN 12 Malang. Results of a small group trial with subjects 12 students obtained 85.10% and the percentage of trials with a large group of 30 students obtained the data subject by 87.46%. Based on the results of expert testing and field tests, it can be concluded that the model is a valid exercise smash volleyball used in extracurricular SMPN 12 Malang.Key words: Development, training models, smash, volleyball